Structural Transformation and Poverty Eradication in East Java (A Panel Data Approach of 38 Counties) - Rifa'i, Achmad; Listiono (Journal of Developing Economies, 2021)
The characteristic of structural transformation is a decrease in the share of agriculture followed by an increase in the industry share in the economy. Sometimes, the share of services to the economy increases more rapidly than the share of the industry, called immature structural transformation. This study aims to analyze the structural transformation process in East Java and its impact on poverty alleviation. Panel data for 38 districts/cities used from the Statistics Indonesia (BPS) during the 2012-2015 period. The estimation results revealed empirically that the service sector has a significant impact on reducing poverty in East Java. This research argues that East Java has experienced immature structural transformation seen from the stagnation of the industry's share of the economy. It is supposed that the role of the industrial sector is not significant, while the service sector is better to reduce poverty. Keywords: Structural Transformation, Poverty, East Java, Panel Data JEL: B22, I32, L16